Forbearance vs foreclosure in a general equilibrium model - Bianca Barbaro; Patrizio Tirelli (European Central Bank (ECB), 2021)
We build a business cycle model characterized by endogenous firms dynamics, where banks may prefer debt renegotiation, i.e. non-performing exposures, to outright borrowers default. We find that debt renegotiations only do not have adverse effects in the event of financial crisis episodes, but a large share of non-performing firms is associated with a sharp deterioration of economic activity in two cases. First, if there are congestion effects in banks ability to monitor non-performing loans. Second, if such loans adversely affect the commercial banks' moral hazard problem due to their opacity. Aggressive interest rate reductions and quantitative easing limit defaults and the output contraction caused by a financial crisis, without adverse effects on the entry of new, more productive firms. The model shows that the observed long-run trend in the share of non-performing loans might be caused by the persistent reduction in technological advancements which drive firm entry rates and firms turnover.
Keywords: E32; E44; E50; E58; 330; Non-Performing Loans; DSGE Model; Financial Frictions; Quantitative Easing; Firms Entry